Assessing public preferences for deep sea ecosystem conservation: a choice experiment in Norway and Scotland. Issue 2 (3rd April 2022) - Ankamah-Yeboah, Isaac; Armstrong, Claire W.; Hynes, Stephen; Xuan, Bui Bich; Simpson, Katherine
ABSTRACT: Recent events around the world have revealed varying degrees of public support for climate change and environmental regulation. Applying a latent class logit model, this study investigates Norwegian and Scottish public's economic support for proposed deep sea management policies for novel attributes, identifying the presence of preference heterogeneity. Marine litter and health of fish stocks were the attributes with the highest values in absolute terms. This was followed by the size of the protected area coverage, whilst the creation of jobs was the least valued. The results highlight public support for the further collective action required by the EU in moving beyond the 2020 objective of achieving good environmental status of Europe's seas, despite the low WTP values of the minority classes in each country.